[updated from 2017] District nutrition profiles for India - CGIAR Research Program on Agriculture for Nutrition and Health (2018)
The profiles are online. This link takes users to an interactive map where they can navigate to the desired state name and get the Nutrition Profile for that specific district REMOVE. This was re-submitted in error. There were no new updates since 2017.